2023
DOI: 10.1002/mde.3897
|View full text |Cite
|
Sign up to set email alerts
|

Boundary spanning strategy and tacit knowledge recombination: Analysis of joint‐patent networks of patent‐intensive firms

Abstract: This paper collects 103 sample firms' 2015 to 2019 data through data envelopment analysis to measure their technical innovation performance and social network analysis to build joint‐patent networks and explore knowledge‐creating alliance relationships. The article highlights how tacit knowledge recombination works as a mechanism of boundary spanning. It emphasizes the significance of strategic balancing networks' position to improve technical innovation performance and competitiveness of patent‐intensive (PI)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(5 citation statements)
references
References 144 publications
(188 reference statements)
0
5
0
Order By: Relevance
“…As such, it is difficult to maintain partnerships as the firm needs to find dissimilar but needed knowledge (Dong et al, 2018;Van Beers and Zand, 2014). Meanwhile, excessive relevance results in knowledge leakage (Frishammar et al, 2015), which will reduce uniqueness of internal knowledge resources and raises focal firm's concerns regarding the network (Guo et al, 2021;Fawad Sharif et al, 2020;Jiang and Zhang, 2023). Studies have showed that intense relevance in knowledge resource will end up in redundant information, which curtails focal firm's ability to process accurate information and adversely affects strategic objectives, which is not conducive for a stable network (de Leeuw et al, 2014;Nadia et al, 2021).…”
Section: Partner Type Relevance and Network Stabilitymentioning
confidence: 99%
See 4 more Smart Citations
“…As such, it is difficult to maintain partnerships as the firm needs to find dissimilar but needed knowledge (Dong et al, 2018;Van Beers and Zand, 2014). Meanwhile, excessive relevance results in knowledge leakage (Frishammar et al, 2015), which will reduce uniqueness of internal knowledge resources and raises focal firm's concerns regarding the network (Guo et al, 2021;Fawad Sharif et al, 2020;Jiang and Zhang, 2023). Studies have showed that intense relevance in knowledge resource will end up in redundant information, which curtails focal firm's ability to process accurate information and adversely affects strategic objectives, which is not conducive for a stable network (de Leeuw et al, 2014;Nadia et al, 2021).…”
Section: Partner Type Relevance and Network Stabilitymentioning
confidence: 99%
“…Knowledge accession is critical for enhancing product creativity and uniqueness; partners obtain necessary resources and undertake a range of specialized tasks and skills needed for breakthroughs in technical dilemmas (Carnabuci and Operti, 2013;Hagedoorn et al, 2018). Obtaining more diversified knowledge broadens scope of technical resources, improves degree of product differentiation and acquires more knowledge to improve their R&D speed (Jiang and Zhang, 2023). Stuart (2000) found that higher number of partners will gather more technical resources to yield maximum efficiency in innovation driven projects.…”
Section: The Mediating Role Of Knowledge Recombinationmentioning
confidence: 99%
See 3 more Smart Citations